Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Effect of boiling and in vitro digestion on nutritional quality and metabolomic profiles of bambara groundnut and soybean protein isolates - Mingmin Chen; Shir Reen Chia; Zhen Zheng; Wei Han Foo; Lin Chen (Food Hydrocolloids, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Salinity shapes biofilm community to promote partial nitrification and sulfamethoxazole removal in membrane-aerated biofilm reactors - Zhi-Cheng Wu; Yu-Lin Han; Chen-Wei Zheng; He-Ping Zhao (Journal of Water Process Engineering, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Integrative study of acute ammonia exposure on the skin of the Striped catfish (Pangasianodon hypophthalmus) - Wei-Hsuan Hsiao; Shun-Yi Lin; Ying-Hsien Wu; Han-Chen Ho; Tsunglin Liu; Liang-Chun Wang (Aquatic Toxicology, 2026)

Evolution of swine influenza surveillance and one health governance in Taiwan: from zoonotic risk management to integrated preparedness - Cheng-Han Lin; Tzu-Min Lin; Meng-Wei Lin; Chih-Sheng Lin (Veterinary Research Communications, 2026)

Full-field deformation quantification of underground tunnels using SLAM LiDAR point cloud based on unsupervised neural implicit learning - Zhen Han; Wei Lin; Qian Li; Danqi Li (Tunnelling and Underground Space Technology, 2026)

Optimized design of ozone microbubble aeration reactor to enhance the removal of dissolved organic matter: A pilot-scale study on drinking water treatment - Jinmin Su; Tao Lin; Han Chen; Wei Liu; Yuchen Wang; Yimu Qiao (Journal of Environmental Management, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Wave-adaptive floating platform for hybrid triboelectric-electromagnetic energy harvesting toward marine IoT systems - Shilin Wu; Lingyu Wan; Erming Su; Gaojian Wei; Wei Tang; Siyan Pan; Jiaqi Han; Zhong Lin Wang; Leo N.Y. Cao (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Postharvest properties and metabolomic profiling of cucumbers treated with hydrogen sulfide under low-temperature storage - Wei Han Foo; Mingmin Chen; Xue Zhao; Yu Xuan Lim; Lin Chen (Food Chemistry, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

Exploring genetic structure and habitat suitability of the masked palm civet (Paguma larvata) in Taiwan - Shih-Wei Chang; Tzong-Han Lin; Chi-Li Tsai; Hui-Yun Tseng (Mammalian Biology, 2026)

Microplastic contamination in giant tiger prawn and greasyback shrimp from Malaysian waters - Wei Lin Wong; Tony Hadibarata; Risky Ayu Kristanti; Undang Hernawan; Budi Kurniawan; Mohammad Noor Hazwan Jusoh; Josfirin Uding Rangga; Han Kiat Chin; Anisa Ratnasari (Environmental Sustainability, 2026)
Microplastics (MPs) are ubiquitous contaminants in the marine environment. The potential pathway through the food web to humans is a general public concern. Commonly consumed marine organisms have never been studied for the presence of MPs as an entry route into the food chain. This study selected Penaeus monodon (tiger prawn) and Metapenaeus ensis (greasyback shrimp) because of their commercial importance, high consumption rates, and consistent availability in Miri, Sarawak, Malaysia. Samples were collected from major fish markets supplied by both coastal fisheries and aquaculture farms. The gastrointestinal tracts of both species were analyzed under a microscope, and Attenuated Total Reflectance Fourier-Transform Infrared (ATR–FTIR) spectroscopy was performed on suspected MPs based on their physical characteristics. All samples contained plastic: 280 ± 91 pieces/kg wet weight for P. monodon and 457 ± 171 pieces/kg for M. ensis . Fibers were the dominant shape of the MPs observed, followed by fragments and pellets; black was also the dominant color. Most of the particles determined by size were within 500 to 1000 μm in dimension. Polyester and polystyrene were the two major types of polymers by the FTIR analysis. This calls for urgent reinforcement in food safety measures accompanied by environmental policy interventions directed towards microplastic contamination in seafood that encapsulates potential health risk avenues to consumers as well as broader ecological impacts.

Bimetallic MOF/3D exosomes-loaded gelatin-dialdehyde starch hydrogel coating: Multimodal regulation of the bone-implant interface - Hui Su; Jian Yin; Jialu Wei; Hao Yang; Pengde Han; Zhangping Wang; He Lin; Lei Xie; Xiao Huang; Jinping Lan; Yong Huang (Chemical Engineering Journal, 2026)

Fracture evolution and mechanical response of coal with damage induced by oil-gas seepage - Yawu Shao; Wei Yao; Lei Zhu; Gang Han; Haifei Lin; Hu Liu; Jiahao Xie; Mingming Sun; Jin Wang (Bulletin of Engineering Geology and the Environment, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

Assessing the climate and environmental benefits of new urban district development using mobile monitoring and gradient boosting decision trees - Li Han; Ke Li; Lin Luo; Yuejing Gao; Wei Ding; Jingyuan Zhao (Urban Climate, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Machine-learning-guided extraction optimization and physicochemical characteristic of GRAS microalgae proteins for sustainable food applications - Wei Han Foo; Mingmin Chen; Yu Xuan Lim; Lin Chen (Food Hydrocolloids, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Precipitation reduction mitigates the negative impact of nitrogen deposition on soil nitrogen fixation in subtropical Chinese fir plantations - Fengyi Han; Yongxin Lin; Maokui Lyu; Hang-Wei Hu; Xiangyin Ni; Qiufang Zhang; Jinsheng Xie; Ji-Zheng He; Peter M. Homyak (Science China Life Sciences, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Permeability Evolution and Failure Behavior of Coal Under Coupled Oil–Gas Porous Flow and Mining-Induced Stress - Yawu Shao; Lei Zhu; Gang Han; Haifei Lin; Wei Yao; Hu Liu; Jiahao Xie; Tao You; Mingming Sun; Jin Wang (Rock Mechanics and Rock Engineering, 2026)

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Co-occurrence and regulation of nanoplastics and typical flame retardant in anammox process: Potential risk and molecular mechanism - Jing-Ao Jin; Na-Na Han; Wei-Lin Guo; Qiu-You Xu; Jiao-Jiao Wang; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Green and scalable design of plant-based MoS2-OA Pickering nanofluids for simultaneous friction reduction and heat dissipation in sustainable metalworking - Wei Wang; Deping Xia; Xin Wang; Hualin Lin; Jingzhou Liu; Shuai Huang; Mingan Zhou; Bin Dai; Sheng Han (Journal of Environmental Chemical Engineering, 2026)

Statistical optimization of biochar production via high-temperature carbonization through Taguchi and principal component analysis approaches - Jamin Jamir Escalante; Wei-Hsin Chen; Chien-Yuan Su; Po-Han Li; Kun-Yi Andrew Lin; Kanit Manatura (Fuel, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

CoFe Prussian blue analogue photothermal self-healing coating for resistance to corrosion, UV degradation and mold - Yang Han; Qiang Sun; Lin Cao; Han Li; Lankun Liu; Zihan Li; Wei Wang (Chemical Engineering Journal, 2026)

Eco-Friendly Dust Control Strategies: A Critical Review of Chemical Suppressants for Sustainable Environmental Management - Nini Wang; Zhihui Huang; Lin Yang; Tingting Han; Nan Wang; Xiangpeng Meng; Wei Zhang (Water, Air, & Soil Pollution, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Distinct ecological strategies drive divergent assembly: strong deterministic specialization in fungi versus higher stochastic adaptability in archaea in coastal salt marshes - Kaiqi Lu; Yuan Su; Xiaodao Wei; Yam Prasad Dhital; Md. Jaker Hossain; Qiuxun Lin; Han Su (Frontiers in Marine Science, 2026)
Coastal salt marshes are among the most productive ecosystems on Earth, playing a critical role in “Blue Carbon” sequestration and biogeochemical cycling. However, in this dynamic habitat characterized by strong environmental gradients, the mechanisms by which microorganisms from different domains—Archaea and Fungi—respond to spatiotemporal environmental rhythms to maintain community stability remain poorly understood. This study systematically investigated the community composition, assembly mechanisms, and niche characteristics of archaea and fungi in sediments across a broad latitudinal gradient and seasonal scales along the coast of China. The results revealed distinct and contrasting ecological strategies between these two microbial groups. Fungal communities exhibited high environmental sensitivity. In contrast, archaeal communities demonstrated remarkable habitat resilience. This study highlights the contrasting mechanisms where archaea maintain structural stability through a higher relative proportion of generalists and stochastic resilience, while fungi respond to environmental changes through a more extreme reliance on niche specialization and deterministic turnover, providing a new theoretical framework for understanding the maintenance of multi-domain microbial assemblages in coastal wetlands under global climate change.

A review of researches on carbon dioxide emission accounting and evaluation - Feng Lin; Honglei Ding; Wenhuan Wang; Chaojie Wei; Fan Han; Yifeng Xu; Ziyi Zhang; Jie Song; Weiguo Pan (Environment, Development and Sustainability, 2026)

Synergistic pyrogenic carbon-microbial dehalogenator taking the “forever” out of “forever chemicals” - Kaikai Zhang; Jiayu Deng; Wei-Han Lin; Caide Huang; Deyi Hou (Water Research, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Dietary carbohydrate fuels a metabolic strategy for osmotic adaptation, enhancing growth and resilience of Litopenaeus vannamei in low-salinity water - Zhao Li; Zhi Luo; Sheng-Wei Lin; Feng-Lu Han; Chang Xu; Er-Chao Li (Aquaculture International, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

Mechanisms of cell death in Klebsiella pneumoniae-induced acute splenic injury in Aquarana catesbeiana - Han Lin; Hua Li; Kesong Chen; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2026)

SUMO1 promotes malignancy and chemoresistance in colorectal cancer: Clinical and functional evidence - Anran Xu; Tianyuan Tan; Lin Yuan; Wei Yan; Yang Han; Su Lu (Tissue and Cell, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Can membrane aerated biofilm reactor (MABR) realize more efficient simultaneous partial nitrification and denitrification than conventional biofilm under low COD/N? - Zixuan Yan; Xushen Han; Haiyang He; Yuqing Lin; Yan Jin; Wei Jiang; Han Zhang; Xingfu Song (Journal of Cleaner Production, 2026)

Optimizing collaborative management decision-making in large watersheds through seasonal dynamic water quality diagnosis - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Cleaner Production, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

A novel mainstream application of aerobic granular sludge for nitrite supply to Anammox: insights from granule size and microbial stratification - Zongshuo Han; Xiaoying Zheng; Wenfei Li; Haidong He; Yi Fan; Tao Lin; Wei Chen (Journal of Cleaner Production, 2026)

High performance CeO2/Mn2O3-Mn5O8 catalysts from Mn-MIL-100 for benzene catalytic oxidation - Hongxiang Chen; Biliang Lin; Guiping Jiao; Wenying Wei; Ning Zhao; Yanwei Han; Weiyan Zhu; Yifan Zhang; Yong Wang (Journal of Environmental Chemical Engineering, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Closed-loop recovery under mild conditions of end-life wind turbine blade via synergy of responsive deep eutectic solvent-ZnCl2 - Wei Lu; Lin Ma; Ludovico Cademartiri; Bonan Zhang; Yijie Li; Quanming Ren; Song Dai; Qingsong Zhang; Bo Han (Chemical Engineering Journal, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

Combustion acceleration in Al/CuO nanothermite films via gap-induced particle-advection mechanism - Xiaoxia Ma; Changcheng Bao; Lin Shi; Junzhe Xu; Wei Liu; Jimin Han; Li Yang (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Implementation of a Deep Learning Ensemble Framework Based on Bidirectional Message Queues - Xin-Jian Wei; Wu-Yang Yang; Xin Xu; Hai-Shan Li; Nan Wang; Wei-Sheng Wang; Han-Wei Lin; Chen Wang (Applied Geophysics, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Morphological and molecular evidence reveal the Sarotherodon melanotheron invasion off Taiwan, East Asia - Yen-Ting Lin; Yu-Hsiang Lin; You-Wei Shiu; Yu-San Han (Marine Pollution Bulletin, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Two novel TRAF homologs are implicated in the immunological response and interact with IRAK in the Zhikong scallop (Chlamys farreri) - Jiwen Chen; Wei Chen; Yifan Qu; Xiaoxue Lin; Haikun Zhang; Jilv Ma; Jie Cui; Fengchen Liu; Zhongyi Chu; Yue Zhao; Yabin Wang; Yaqiong Liu; et al. (Aquaculture, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Assessing the effects of climate and land use change on nitrate loads using the SWAT-MODFLOW-RT3D model - Lu Zhang; Yunfeng Dai; Jiangbo Han; Xue Li; Jin Lin; Wei Li; Shaoyi Feng; Peng liu (Journal of Hydrology, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Three eagles with one arrow: Multimode and dynamic luminescence from single non-conjugated polymer system induced by aromatic β-diketone - Wei Lv; Jingwen Han; Fan Wu; Shuaiqi Wang; Meijuan Lin; Qidan Ling; Zhenghuan Lin (Chemical Engineering Journal, 2026)

Optimization of bacterial nanocellulose synthesis using surfactants for immobilization of Saccharomyces cerevisiae to enhance resistance to lignocellulose-derived inhibitor - Yetong Feng; Dingkang Wei; Shuai Han; Peihong Chen; Jie Liu; Tao Chen; Yiran Yan; Yang Bai; Linxu Chen; Jianqun Lin; Jianqiang Lin; Zixiang Xu; et al. (Bioresource Technology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Multistep-Ahead Forecasting of Chlorophyll Concentration Based on Dynamic Collaborative Attention Network - Lei Wang; Guodong Han; Ping Wu; Jie Mei; Zhenyu Lin; Shengming Cheng; Xianhua Wei; Xu Yang; Chuxu Xiong; Shaoyang Dai; Ying Zhao (Journal of Marine Science and Engineering, 2025)
Multistep-ahead forecasting of chlorophyll concentration is of great significance in red tide early warning systems. Existing methods often neglect the potential adverse interactions between non-predictive variables and chlorophyll while failing to fully utilize the effective information in historical decoder units. To address these issues, this paper proposes a Dynamic Collaborative Attention Network (DCAN) model for chlorophyll concentration forecasting, which consists of two components: a Two-Stage Variable Embedding Network (TSVEN) and a Dynamic Attention Network (DyAN). The TSVEN can identify the non-predictive variables that have the most significant impact on chlorophyll changes and generate corresponding spatial vectors from them, thereby alleviating the information conflict between chlorophyll and non-predictive variables. The DyAN integrates a context attention module and a filtering gate mechanism. The former effectively extends the forecasting time range by dynamically retrieving historical decoder states, while the latter selectively integrates historical decoder information, thereby improving the reliability of model decisions and prediction accuracy. Experimental results based on real datasets show that the proposed model outperforms the current state-of-the-art methods in chlorophyll concentration forecasting tasks and exhibits good interpretability.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Numerical modelling of the through-draught induced by traveling trains in subways and its impact on airborne droplet transmission in compartments - Tiantian Wang; Jiyu Yao; Wei Han; Yibin Lu; Zhe Chen; Fangcheng Shi; Zhang Lin (Process Safety and Environmental Protection, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Do river-valley breezes enhance evaporation over the Three Gorges Reservoir during periods with negative water-to-air temperature differences? - Songjun Han; Baozhong Zhang; Lei Wang; Jiajia Liu; Weijie Wang; Taotao Lin; Jidong Wang; Liang Wei; Zhijun Jia (Journal of Hydrology, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Biocontrol potential and cryopreservation of marine ciliates for sustainable management of bacterial pathogens in aquaculture - Xin-Long Liu; Sin-Wei Lin; Wei-Yu Yeh; Hung-Yun Lin; Han-Jia Lin (Fish & Shellfish Immunology, 2025)

Acute skin responses to ammonia in striped catfish (Pangasianodon hypophthalmus) unveil a potential damage-buffering mechanism - Wei-Hsuan Hsiao; Shun-Yi Lin; Tsung-Lin Liu; Han-Chen Ho; Liang-Chun Wang (Fish & Shellfish Immunology, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Efficient preparation of large-area anisotropic graphite films with high thermal conductivity and excellent electromagnetic shielding performance - Zhihong Han; Mingyi Tan; Daming Chen; Wenzheng Zhang; Zhipeng Lin; Jiahui Zhou; Yuhao Fang; Shengze Zhang; Qihong Wei; Xinghong Zhang; Wenbo Han (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Microalgal-bacterial granular sludge enhances oxytetracycline removal: Microbial responses, degradation pathways, and adaptive mechanisms - Yunqing Li; Xiaoying Zheng; Haidong He; Ruijie Hu; Zongshuo Han; Jiaqing Tao; Tao Lin; Wei Chen (Journal of Hazardous Materials, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Preparation of sludge derived fuels for co-incineration in waste incinerators: Industrial tests and life cycle assessment - Yanfei Lin; Hanqiao Liu; Guoxia Wei; Tong Li; Qianlong Han; Zilu Liu; Xinrui Su; Yifan Chen (Sustainable Production and Consumption, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Chemical constituents isolated from leaves of seashore plant Aglaia rimosa - Jing-Ru Weng; Jui-Hsin Su; Ping-Jyun Sung; Wei-Yu Lin; Zhen-Hong Han; You-Ying Chen; Chun-Lin Chen (Phytochemistry Letters, 2025)

Research on the calculation methods for time-domain friction excitation force in mixed lubrication contact between ship shaft and bearings - Chang-Gang Lin; Hao Wang; Can Sima; Yan-Feng Han; Wei-peng Zhang; Ming-Song Zou (Ocean Engineering, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

Gas content and fracability in deep marine shales: Insights from laminar heterogeneity and reservoir characteristics - Xiao Xiao; Jizhen Zhang; Jianguo Wang; Wei Guo; Wei Lin; Denglin Han; Chenchen Wang (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

Shrinkage effect of innovative group studs configuration on steel-UHPC composite deck in a girder - Sheraz Abbas; Han Xiao; Chen Xu; Wei Wang; Zhipin Lin (Engineering Structures, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Chitosan-based Janus dressing with asymmetric wettability for rapid hemostasis, antibacterial protection, and tissue regeneration in hemorrhagic wound management - Jiyuan Wang; Haowen Ye; Kaitong He; Weikang Jiang; Wei Lan; Zu’an Zeng; Peiran Lin; Han Wang; Botao Gao; Wenlong Wang; Yadong Tang (Carbohydrate Polymers, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Multifunctional Cu-engineered NH2-MIL-125Ti@ZnIn2S4 heterojunction with dual-channel H2O2 activation for ultrafast water-mediated Cr(VI) photoreduction - Guangyuan Chen; Wei Han; Chenyang Lin; Yubao Li; Shijian Zhou; Yan Kong (Chemical Engineering Journal, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

SiO2 particles induce pulmonary fibrosis by modulating NLRP3 through the ROS/Keap1/Nrf2 signaling pathway in rats - Shuang Li; Wei-Lei Gong; Lin Liu; Bo Shao; Shun-Li Jiang; Huan Li; Ye Song; Gui-Zhi Han; Zhao-Qiang Zhang (Food and Chemical Toxicology, 2025)

Cobalt-modification on UiO-bpydc MOF facilitates ligand-to-metal charge transfer for superior visible-light photocatalytic degradation of refractory fluoroquinolone antibiotics - Kaichun Lin; Jingjun Qin; Zhang Liu; Weicheng Xu; Meng Li; Yuanzhi Zheng; Wei Han; Guangying Zhou; Jianzhang Fang; Zhanqiang Fang; Feng Peng; King Lun Yeung (Environmental Research, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Antiviral activity of epicatechin against Singapore grouper iridovirus in vitro and in vivo - Lin Huang; Jihui Kuang; Jieying Yu; Qing Yu; Weiqiang Xu; Mingzhu Liu; Yunyi Wei; Shuyu Han; Yanhua Huang; Pengfei Li (Fish & Shellfish Immunology, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Standing crop and size structure of phytoplankton are strongly regulated by the turbidity maximum in the macrotidal Qiantang River estuary-Hangzhou Bay - Lin Zhan; Yuanli Zhu; Chaoxiang Xu; Wei Du; Zhi Yang; Yulu Jiang; Kangning Jia; Ping Du; Chenhua Han; Wei Huang; Jiangning Zeng; Zhibing Jiang (Journal of Oceanology and Limnology, 2025)

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Chemical looping of catalytic methane decomposition with reverse Boudouard reaction using dual functional Ni-FeOx nanoparticle cluster for CO2-negative H2 production - Chien-Wei Wu; Zhi Xuan Law; Yu-Chun Zeng; Kun-Han Lin; De-Hao Tsai (Chemical Engineering Journal, 2025)

CRISPR CLAMP: Attomolar level of multiple miRNAs - Yiming Zhang; Zhi Chen; Songrui Wei; Jing Wang; Yujun Zhang; Huiling Lin; Hai Fu; Yingxia Liu; Qi Gao; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Mechanical response of broken surrounding rock by in-situ expansion of highway tunnel - Hongyun Yang; Jiang Gao; Yongchao Ding; Xiang Chen; Zhi Lin; Han Wu; Yongke Wei; Longwang Xu; Zhanfeng Yang (Bulletin of Engineering Geology and the Environment, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

A novel gravity-driven fixed-bed ceramic membrane filtration (GDFBCM) with critical PAC-MnOx-ceramsite filters for simultaneously removing hazardous manganese and ammonia from groundwater - Dachao Lin; Zhitian Peng; Xiaopeng Zhang; Zhihong Wang; Yi Wu; Xiaobin Ma; Han Zhang; Wei Song; Lifan Liu; Jinxu Nie; Xing Du (Journal of Hazardous Materials, 2025)

Rapid degradation of trace atrazine using ozone microbubbles generated by ceramic membranes: Efficiency, mechanism, and toxicity - Qinyu Han; Tao Lin; Jiayu Du; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Development and validation of deformation-dependent theoretical model for soil arching effect under unloading - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Xiao-Hu Zhang; Han-Lin Wang (Computers and Geotechnics, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Chronological and palaeoecological insights into the Dayakou fauna in Yanjinggou, Chongqing, China: Responses of large mammals to the Early-Middle Pleistocene Climate Transition - Haiqian Hu; Haowen Tong; Fei Han; Hui Dai; Wanbo Huang; Qigao Jiangzuo; Paul Rummy; Xunqian Wang; Yu Lin; Guangbiao Wei (Quaternary Science Reviews, 2025)

Enhancing hexavalent chromium stable reduction via sodium alginate encapsulation of newly isolated fungal and bacterial consortia - Obey Kudakwashe Zveushe; Jackson Nkoh Nkoh; Víctor Resco de Dios; Tendai Terence Manjoro; Fidèle Suanon; Hengxing Zhang; Wenfang Chen; Lin Lin; Lei Zhou; Wei Zhang; Frank Sesu; Jin Li; et al. (Journal of Hazardous Materials, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Analytical behaviour of concrete-encased concrete-filled steel tubular (CFST) member under combined compression and shear load - Zhi-Cheng Yang; Lin-Hai Han; Wei Li (Engineering Structures, 2025)

Shrinkage and bending performance of trapezoidal wet joints in steel-UHPC composite decks - Han Xiao; Wei Wang; Chen Xu; Biao Ma; Zhiping Lin; Qingtian Su (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Expanding the pH range of Fenton-like reactions for pollutant degradation: The impact of acidic microenvironments - Shi-Lin Xu; Wei Wang; Yi Song; Rui Tang; Zhen-Hu Hu; Xiao Zhou; Han-Qing Yu (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Degradation of anthracene and phenanthrene by strain Streptomyces sp. M-1 and its application in the treatment of PAHs-contaminated water - Zaimei Zhang; Hui Li; Han Han; Lijian Qin; Wei Lu; Lin Yue; Zongzhen Guo; Shengsong Gao; Shuang Chen; Huie Liu; Dong Wang; Jiqian Wang (Journal of Environmental Management, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

A kinetic study of CO2 and H2O addition on NO formation for ammonia-methanol combustion - Yuzheng Gao; Youping Li; Xianting Wei; Yang Zheng; Shixuan Yang; Qirong Yang; Han Jiang; Yiran Zhang; He Lin (Fuel, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

DTD1 modulates synaptic efficacy by maintaining D-serine and D-aspartate homeostasis - Xiao Liu; Chaojuan Yang; Zhuoran Lin; Jianing Li; Bin Yin; Xuepei Lei; Wei Han; Boqin Qiang; Pengcheng Shu; Chen Zhang; Xiaozhong Peng (Science China Life Sciences, 2025)

Fabrication of Ag based Surface Enhanced Raman Scattering substrates with periodic mask arrays by electron beam deposition - Tian Xing; Jiawei Wang; Jiaqing Wei; Xingxing Du; Ruijin Hong; Chunxian Tao; Qi Wang; Hui Lin; Zhaoxia Han; Dawei Zhang (Analytica Chimica Acta, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Pyrogenic carbon modulating TCE dehalogenation through snorkeling electrons under sulfate-reducing conditions - Kaikai Zhang; Wei-Han Lin; Shanquan Wang; Deyi Hou (Journal of Hazardous Materials, 2024)

Integrating a high-energy activation method for the sustainable treatment of iron smelting slag, phosphogypsum, and arsenic-contaminated water - Donghui Chen; Jie Tan; Hong Li; Yanmin Lin; Fangming Nan; Qingwen Han; Wei Zhan (Journal of Environmental Chemical Engineering, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Covalent metal–organic porous polymer on ZIF-67 realize anti-UV and highly stressed flame retardant epoxy composites - Jin Cao; Shangxian Chen; Zhengde Han; Ye-Tang Pan; Yichao Lin; Wei Wang; Rongjie Yang (Chemical Engineering Journal, 2024)

MST1R Gene Variants Predispose Individuals to Tetralogy of Fallot - Zhiyu Feng; Xianghui Huang; Yuan Gao; Han Gao; Weilan Na; Chaozhong Tan; Shaojie Min; Yuquan Lu; Quannan Zhuang; Siyi Lin; Xiaojing Ma; Weicheng Chen; et al. (Phenomics, 2024)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart malformation. While a few susceptibility genes for TOF have been identified, research on the genetic basis of TOF is limited. The Macrophage stimulating 1 receptor ( MST1R ) gene encodes the macrophage-stimulating protein receptor with tyrosine phosphatase activity that is involved in immune defense. In this study, we performed whole-exome sequencing (WES) on 10 TOF families and 50 sporadic TOF patients and identified a recessive homozygous missense mutation in MST1R , c.T2009G: p.V670G, in two offspring with TOF in a single family. Targeted sequencing of the MST1R gene showed enrichment for rare variants in 417 TOF patients compared with East Asians in Genome Aggregation Database Version 2 (gnomADv2_EAS). MST1R -deficient human induced pluripotent stem cells (hiPSCs) maintained normal pluripotency but differentiated into non-functional cardiomyocytes (CMs). Taken together, our findings indicate that MST1R may play a critical role in cardiac differentiation and genetic variations in MST1R may be associated with the pathogenesis of TOF.

Well Logging Stratigraphic Correlation Algorithm Based on Semantic Segmentation - Cai-zhi Wang; Xing-yun Wei; Hai-xia Pan; Lin-feng Han; Hao Wang; Hong-qiang Wang; Han Zhao (Applied Geophysics, 2024)

Vulnerability of Global Pine Forestry's Carbon Sink to an Invasive Pathogen–Vector System - Jiao Zhou; Jingjing Du; Luís Bonifácio; Wandong Yin; Lin Huang; Jing Ning; Dongbo Han; Jiafu Hu; Wei Song; Lilin Zhao (Global Change Biology, 2024)
The substantial contribution of northern forest growth to the global increase of biomass carbon stock is well documented. However, the ecological consequences of pest‐ and disease‐related losses in these forests have not received comparable attention. This study highlights that pine species are major contributors to carbon stocks in Northern Hemisphere. The total carbon storage of Pinus in the Northern Hemisphere was estimated at 70,726 teragrams of carbon (TgC; 17.7% of the total forest carbon 478,012 TgC), accounting for 4.9%, 28.4%, and 12.5% of the total carbon storage in the forests of Asia, Europe, and North America, respectively. However, pine trees were under threat from an invasive complex involving the pine wood nematode ( Bursaphelenchus xylophilus ) and Japanese pine sawyer beetle ( Monochamus spp.). Since 1977, this complex resulted in a carbon sink deficit of 1857 TgC (18% of the carbon currently stored in Europe's live tree biomass) in northern pine ecosystems. The carbon losses attributed to B. xylophilus exceeded those caused by wildfires, which are typically regarded as the primary factor of forest disturbances. Furthermore, the contributions of environmental variables indicate that the expected northward shift in precipitation patterns will exacerbate B. xylophilus threats, endangering 78% of the boreal forests across Eurasia by 2100. Among these high‐risk areas, 62% contributed significantly to global carbon sink, and 42% was protected forests. Following the present trend, carbon losses caused by the B. xylophilus complex could exceed 39% of the total carbon storage in terrestrial ecosystems. This study provides comprehensive datasets that detail the global distribution and high‐risk habitats of pine species and B. xylophilus vector beetles in affected countries. Our findings underscore the substantial risk of carbon losses posed by B. xylophilus to northern pine forests, with potential implications for global carbon dynamics and the achievement of international goals related to “carbon peak” and “carbon neutrality.”

Application of a novel machine learning model for the prediction and optimization of anti-blast performance of sandwich honeycomb blast walls - Lei Yang; Hong Lin; Longcheng Wei; Chang Han; Hao Xu; Hassan Karampour (Ocean Engineering, 2024)

The bifunctional impact of polylactic acid microplastics on composting processes and soil-plant systems: Dynamics of microbial communities and ecological niche competition - Yufan Wang; Yiqiong Zhang; Zhouchang Zhang; Qing Liu; Tengqi Xu; Jiaxi Liu; Siqi Han; Tianjiao Song; Li Li; Xiaomin Wei; Yanbing Lin (Journal of Hazardous Materials, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Comparative study on environmental and economic assessment of straw heating across administrative areas scale of rural China - Tong Li; Guoxia Wei; Hanqiao Liu; Hailong Zhao; Yuwen Zhu; Yanfei Lin; Qianlong Han; Yifan Chen; Yanzhang Wang (The International Journal of Life Cycle Assessment, 2024)

The influences of ApoE isoforms on endothelial adherens junctions and actin cytoskeleton responding to mCRP - Zhengrong Zhang; Weiwei Lin; Qini Gan; Maohua Lei; Bin Gong; Chao Zhang; Jessica Salles Henrique; Jingyan Han; Hua Tian; Qiushan Tao; Lawrence A. Potempa; Thor D. Stein; et al. (Angiogenesis, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

An Anisotropic Thermal–Mechanical Coupling Failure Criterion for Slate - Meng-Chia Weng; Shih-Shiang Lin; Chih-Shan Lee; Wei-Han Wu; Jia Han Li; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2024)
This study investigates the thermal–mechanical behavior of slates in geothermal reservoirs and establishes an anisotropic thermal–mechanical coupling failure criterion. Slate samples obtained from a geothermal site were subjected to a series of direct-shear and triaxial-compression tests at various confining pressures and temperatures. The results showed that the orientation angle within a specific range caused shear sliding failure of the slate, primarily due to foliation strength; beyond this range, intrinsic rock properties led to different failure modes. Elevated temperatures significantly diminished the strength anisotropy of the slate. These findings provided a foundation for the development of an anisotropic thermal–mechanical coupling failure criterion. The validity of the proposed criterion, which incorporates both the orientation angle and thermal degradation effects, was demonstrated through experimental results. A three-dimensional surface diagram was constructed to visualize the relationship between the temperature, orientation angle, and failure principal stress, highlighting the anisotropic thermal-degradation characteristics of the slate under varying confining pressures. This study enhances the understanding of the thermal–mechanical behavior of these materials in geothermal reservoirs.

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Investigation on the induced electrical wakes generated by underwater vehicles - Qing Chen; Yimin Xuan; Qunqing Lin; Yuge Han; Kai Wei (Ocean Engineering, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Co-Al hydrotalcite assembled nanofibers to enhance corrosion inhibition and effective Cl− adsorption for long-term corrosion protection - Lin Cao; Jinming Piao; Wei Wang; Weijie Fan; Dongxiao Han; Yantong Pei; Ye Chen; Yue Zhang (Chemical Engineering Journal, 2024)

Anisotropy measurements and characterization of the Qingshankou shale - Qing-feng Li; Xue-hong Yan; Wei-lin Yan; Li Ren; Peng Wang; Jian-qiang Han; Xue Xia; Hao Chen (Applied Geophysics, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Deep learning-based dispersion prediction model for hazardous chemical leaks using transfer learning - Xiaoyi Han; Jiaxing Zhu; Haosen Li; Wei Xu; Junjie Feng; Lin Hao; Hongyuan Wei (Process Safety and Environmental Protection, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

A novel EGCG-Histidine complex improves gelling and physicochemical properties of porcine myofibrillar proteins: Insight into underlying mechanisms - Xiao Guo; Renzheng Wang; Bofu Han; Wei Shao; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Achieving ultra-high cycle stability of ZnCo2O4/SrF2-0.2 as positive electrode materials for supercapacitors: Realization and investigation of underlying mechanisms - Xiaxin Lei; Yan Zhang; Jiani Han; Xiaohong Su; Lin Xue; Wei Guo; Yongjia Zhang (Chemical Engineering Journal, 2024)

Targeting IGF2BP1 alleviated benzene hematotoxicity by reprogramming BCAA metabolism and fatty acid oxidation - Jingyu Wang; Lin Han; Ziyan Liu; Wei Zhang; Lei Zhang; Jiaru Jing; Ai Gao (Chemico-Biological Interactions, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Impact of ocean mixed layer depth on tropical cyclone characteristics: a numerical investigation - Yalan Zhang; Kaifeng Han; Yuan Sun; Yanluan Lin; Panmao Zhai; Xinwen Guo; Wei Zhong (Frontiers in Marine Science, 2024)
Introduction The impact of upper-ocean temperature on tropical cyclone (TC) activity is an open issue. Compared to the attention devoted to the effect of sea-surface temperature (SST) on TC activities, much less is known about the effect of ocean mixed layer depth (OMLD) on TC activities, which is determined by the ocean temperature below the surface. Methods In this study, a series of idealized numerical experiments were conducted to investigate the possible responses of TC activities to OMLD. Results It was found that while OMLD exerts a minor influence on TC track, it evidently affects TC intensity, size, and destructiveness before reaching a certain OMLD threshold (approximately 15 m). Once the OMLD exceeds the threshold, changes in TC intensity, size, and destructiveness become marginal with further increase in OMLD. The threshold of OMLD is largely determined by TC intensity, which in turn is dictated by surface wind speed. Discussion Specifically, before reaching the threshold of OMLD, the surface wind, namely TC-related surface wind, may bring the cold water from below the OMLD, and effectively decreases the upper ocean temperature (including the SST). As OMLD increases, the effect of surface wind on SST cooling gradually decreases, leading to an increase of SST below the TC. Subsequently, the SST increase leads to more surface enthalpy flux (SEF) input into the TC by increasing air-sea temperature and moisture differences. By altering TC's thermodynamic and dynamic structures, the increase of SEF eventually results in the increase of TC intensity and size, and thus its destructiveness.

Comparative Assessment of the Environmental and Economic Performance of Two Straw Utilization Pathways in China - Tong Li; Guoxia Wei; Hanqiao Liu; Yuwen Zhu; Yanfei Lin; Qianlong Han (BioEnergy Research, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

Evaluating the anisotropic thermal–mechanical coupling strength of slate: A discrete element method approach - Minh-Triet Pham; Meng-Chia Weng; Hoang-Khanh Le; Shih-Shiang Lin; Wei-Han Wu (Computers and Geotechnics, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Competitive-like binding between carbon black and CTNNB1 to ΔNp63 interpreting the abnormal respiratory epithelial repair after injury - Xiaoran Wei; Nan Liu; Yawen Feng; Hongmei Wang; Weizhong Han; Min Zhuang; Hongna Zhang; Wei Gao; Yongfeng Lin; Xiaowen Tang; Yuxin Zheng (Science of The Total Environment, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Environmental and economic analysis of the transformation of paper mill sludge treatment technologies in China - Yanfei Lin; Guoxia Wei; Hanqiao Liu; Kai Li; Yuwen Zhu; Qianlong Han; Yunzhen Yang; Yi Lian (Environmental Science and Pollution Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Bioenzyme–nanoenzyme–chromogen all-in-one test strip for convenient and sensitive detection of malathion in water environment - Hanwen Zhang; Jiabin Jin; Xini Wang; Wei Han; Lei Qin; Lin Chen; Xiaoyan Mao; Zhenjiang Liu; Xingwei Xiang (Science of The Total Environment, 2024)

Long-term PM1 exposure and hypertension hospitalization: A causal inference study on a large community-based cohort in South China - Yuqin Zhang; Shirui Chen; Jing Wei; Jie Jiang; Xiao Lin; Ying Wang; Chun Hao; Wenjing Wu; Zhupei Yuan; Jie Sun; Han Wang; Zhicheng Du; et al. (Science Bulletin, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Advanced oxidation process/coagulation coupled with membrane distillation (AOP/Coag-MD) for efficient ammonia recovery: Elucidating biofouling control performance and mechanism - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Lin Chen; Liang Zhu (Journal of Hazardous Materials, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Glucans and applications in drug delivery - Hewei Lin; Rongze Han; Wei Wu (Carbohydrate Polymers, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Development of magnetic fluorescence aptasensor for sensitive detection of saxitoxin based on Fe3O4@Au-Pt nanozymes - Lin Zhu; Wei Zeng; Yueqing Li; Yu Han; Jing Wei; Long Wu (Science of The Total Environment, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Study on lean combustion of ammonia-hydrogen mixtures in a pre-chamber engine - Jinlu Huo; Tongbin Zhao; He Lin; Jinhua Li; Wei Zhang; Zhen Huang; Dong Han (Fuel, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Chemical composition, sources, and processes of winter haze in Chengdu, China: Insights from integrating the bulk chemical and single particle approaches - Junke Zhang; Wei Sun; Yunfei Su; Xiaoxue Peng; Chunying Chen; Xinyi Fu; Yuhan Long; Gehui Wang; Zhihan Rao; Lin Han; Xiaojuan Huang (Atmospheric Environment, 2024)

A microelectrode electrochemical sensing platform based on heteroatoms doped carbon nanotubes arrays with peroxidase-like activity for in-situ detection in live cell - Yan Zhang; Tao Lin; Minghui Han; Min Hu; Yun Xu; Wei Huang; Fei Xiao; Anshun Zhao (Analytica Chimica Acta, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

UV-induced photodegradation of emerging para-phenylenediamine quinones in aqueous environment: Kinetics, products identification and toxicity assessments - Wei Wang; Guodong Cao; Jing Zhang; Han Qiao; Huankai Li; Biwei Yang; Yanyan Chen; Lin Zhu; Yuecheng Sang; Lei Du; Zongwei Cai (Journal of Hazardous Materials, 2024)

Soil properties and fungal community jointly explain N2O emissions following N and P enrichment in an alpine meadow - Zhenrong Lin; Lina Shi; Xiaoting Wei; Bing Han; Cuoji Peng; Zeying Yao; Yicheng He; Qing Xiao; Xinmin Lu; Yanfang Deng; Huakun Zhou; Kesi Liu; et al. (Environmental Pollution, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Synthesis and antifungal activity of 2,4-dihydroxy-5-methylphenyl ethanone derivatives against phytopathogenic fungi in vitro - Lin Jia; Cui-Ping Zhang; Yi Zhu; Chun-Yan Zhao; Zeng-Hui Han; Dong-Bao Hu; Wei Shi (Phytochemistry Letters, 2024)

Magnetic biochar enhanced copper immobilization in agricultural lands: Insights from adsorption precipitation and redox - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Lin Chen; Liang Zhu (Journal of Environmental Management, 2024)

Fermented Syzygium samarangense leaves mitigate oxidative stress-triggered hepatotoxicity through Nrf2 activation and epigenetic regulation - Ssu-Han Huang; Zi-Han Lin; Tien-Yuan Wu; Guor-Jien Wei; Yen-Chen Tung; Zheng-Yuan Su (Food Bioscience, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Effects of dietary glutamine supplementation on growth performance, intestinal digestive ability, antioxidant status and hepatic lipid accumulation in Xenocypris davidi (Bleeker,1871) - Yuehan Wang; Zuxiang Peng; Lin Yan; Xin Gao; Lin Wu; Shuchang Cui; Mengyuan Zhou; Tongjun Ren; Wei Wang; Shuhao Sun; Yuzhe Han; Hang Sun (Aquaculture International, 2024)

Re-evaluating the impact and mechanism of digital economy on regional pollution intensity from the perspective of spatial spillover - Pei-Ling Yang; Zi-Han Lin; Zhen-Ning Zhu; Feng-Wei Ying (Environmental Science and Pollution Research, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Adapting to seasonal temperature variations: A dynamic multi-subunit strategy for sulfur autotrophic denitrification bioreactors - Yi-Lu Sun; Han-Lin Wang; Huu Hao Ngo; Wenshan Guo; Bing-Jie Ni; Xue-Ning Zhang; Wei Wei (Environmental Research, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Phenotypic characteristics and immune response of Procypris merus following challenge with aquatic isolate of Klebsiella pneumoniae - Wenyu Liao; Dongdong Wei; Mingzhu Liu; Lin Huang; Bingzheng Li; Yunyi Wei; Shuyu Han; Shuaishuai Huang; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2024)
Currently, aquaculture is a relatively mature industry; however, disease problems are continuously threatening the industry and hindering its development to a certain extent. Klebsiella pneumoniae is one of the zoonotic bacteria widely present in different hosts and has caused some degree of harm to the aquaculture industry, posing a potential threat to the water environment and indirectly also affecting human food safety issues. In this study, K. pneumoniae was isolated from the aquaculture environment, named as ELD, and subjected to pathogenic and immunological related studies. The results of the study showed that the strain carries at least four virulence‐related genes, magA , wabG , ureA and uge , and has developed resistance to at least seven antibacterial drugs, such as amoxicillin, doxycycline, rifampicin, and so on. Moreover, the strain is highly pathogenic and is capable of causing systemic clinical foci in Procypris merus . In addition, after infection with K. pneumoniae , the expression of IL‐1β, IL‐8, HSP70 and C2 was upregulated in P. merus as a whole, whereas the expression of TNF‐α did not change significantly in any of the tissues, which might be a kind of immune response of P. merus against K. pneumoniae infection. This study provides an important theoretical basis for the in‐depth exploration of the pathogenic mechanism of K. pneumoniae in fish and the immune response that occurs after the disease is contracted in fish, as well as theoretical support for the development of effective preventive and therapeutic strategies against K. pneumoniae ‐infected aquatic animals in the future.

Study on ecological compensation quotas in different confined areas of coastal zone - A case study of mangrove reserve in shankou, guangxi, China - Xin Nie; Lin He; Zhoupeng Chen; Mengshi Yang; Yuanyuan Li; Xiaowei He; Han Wang; Wei Gao (Ocean & Coastal Management, 2023)

Discriminating the impacts of vegetation greening and climate change on the changes in evapotranspiration and transpiration fraction over the Yellow River Basin - Yangyang Liu; Ziqi Lin; Zijun Wang; Xu Chen; Peidong Han; Bo Wang; Zhenqian Wang; Zhongming Wen; Haijing Shi; Zhixin Zhang; Wei Zhang (Science of The Total Environment, 2023)

Distribution and abundance of oil-degrading bacteria in seawater of the Yellow Sea and Bohai Sea, China - Haolei Shi; Wei Gao; Yunchao Zheng; Lin Yang; Bin Han; Yanchao Zhang; Li Zheng (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Application of novel nanobubble-contained electrolyzed catalytic water to cleanup petroleum-hydrocarbon contaminated soils and groundwater: A pilot-scale and performance evaluation study - Wing-Sze Ho; Wei-Han Lin; Francis Verpoort; Kun-Liang Hong; Jiun-Hau Ou; Chih-Ming Kao (Journal of Environmental Management, 2023)

Effect of hydraulic regime on sulfur-packed bed performance: Denitrification and disproportionation - Yi-Lu Sun; Wei Wei; Huu Hao Ngo; Wen Shan Guo; Xue-Ning Zhang; Bing-Jie Ni; Wei-Qin Zhuang; Han-Lin Wang (Environmental Research, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Probiotics ameliorate benzene-induced systemic inflammation and hematopoietic toxicity by inhibiting Bacteroidaceae-mediated ferroptosis - Lei Zhang; Huiwen Kang; Wei Zhang; JingYu Wang; Ziyan Liu; Jiaru Jing; Lin Han; Ai Gao (Science of The Total Environment, 2023)

Selective fabrication of hydrophilic BiOCl deposition layer on bismuthinite surface for efficient molybdenite/bismuthinite separation - Shangyong Lin; Hongliang Zhang; Xiangsong Meng; Ruolin Wang; Wei Sun; Haisheng Han; Chenyang Zhang (Minerals Engineering, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Vitamin B12 and iron-rich sludge-derived biochar enhanced PFOA biodegradation: Importance of direct inter-species electron transfer and functional microbes - Kaikai Zhang; Jiayu Deng; Wei-Han Lin; Shaogang Hu (Journal of Environmental Management, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Peroxymonosulfate enhanced Fe(III) coagulation coupled with membrane distillation for ammonia recovery: Membrane fouling control process and mechanism - Wucheng Ma; Rui Han; Liang Zhu; Wei Zhang; Hao Zhang; Longjie Jiang; Lin Chen (Desalination, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

One-step desilication-recrystallization towards enhanced diffusion for Ni/ZSM-5-catalyzed n-hexane hydrogenative isomerization - Ye Song; Bo Peng; Ruoyu Wang; Lei Han; Wenhui Zhao; Lei Wang; Haitao Song; Wei Lin (Chemical Engineering Journal, 2023)

Optimizing inorganic carbon and salinity for enhanced biomass and pigment production in Colaconema formosanum: Implications for sustainable carbon sequestration and stress responses - Han-Yang Yeh; Wei-Lung Wang; Yung-Kai Lin; Fan-Hua Nan; Meng-Chou Lee (Bioresource Technology, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Oxidative stress-affected ACSL1 hydroxymethylation triggered benzene hematopoietic toxicity by inflammation and senescence - Ziyan Liu; Xiaoli Guo; Wei Zhang; Jingyu Wang; Lei Zhang; Jiaru Jing; Lin Han; Ai Gao (Food and Chemical Toxicology, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Permanganate activation by glucose-derived carbonaceous materials for highly efficient degradation of phenol and p-nitrophenol: Formation of hydroxyl radicals and multiple roles of carbonaceous materials - Kaikai Zhang; Muhan Qin; Chih-Ming Kao; Jiayu Deng; Jing Guo; Qiong Guo; Jing Hu; Wei-Han Lin (Chemosphere, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

The gut-brain axis involved in polystyrene nanoplastics-induced neurotoxicity via reprogramming the circadian rhythm-related pathways - Huiwen Kang; Wei Zhang; Jiaru Jing; Danyang Huang; Lei Zhang; Jingyu Wang; Lin Han; Ziyan Liu; Ziyan Wang; Ai Gao (Journal of Hazardous Materials, 2023)

Deep removal of fluoride from tungsten smelting wastewater by combined chemical coagulation-electrocoagulation treatment: From laboratory test to pilot test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Meirong Wu; Lei Yang; Huanjun Bao; Jianhua Kang; Haisheng Han; Chenyang Zhang; Wei Sun (Journal of Cleaner Production, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Localized host-rock porosity near sealed fractures at 7 km depth: Geochemical evidence of deep-seated porosity controls - Denglin Han; Jizhen Zhang; Chenchen Wang; Wei Lin; Rui Yuan; Xin Nie; Juan Zhang (Journal of Structural Geology, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

A gluten degrading probiotic Bacillus subtilis LZU-GM relieve adverse effect of gluten additive food and balances gut microbiota in mice - Aman Khan; Shiqing Li; Huawen Han; Wei-Lin Jin; Zhenmin Ling; Jing Ji; Shazia Iram; Pu Liu; Sa Xiao; El-Sayed Salama; Xiangkai Li (Food Research International, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Impact of Cold Spells on Ischemic Stroke Severity and Clinical Outcomes in Tianjin, China - Juanjuan Xue; Chanjuan Wei; Xiaoshuang Xia; Xuemei Qi; Yumeng Gu; Zhongyan Wang; Suqin Han; Lin Wang; Xin Li (Journal of Meteorological Research, 2023)

Comparison of nutritional quality, flesh quality, muscle cellularity, and expression of muscle growth-related genes between wild and recirculating aquaculture system (RAS)-farmed black rockfish (Sebastes schlegelii) - Xin Gao; Haojie Zhai; Zuxiang Peng; Jinxi Yu; Lin Yan; Wei Wang; Tongjun Ren; Yuzhe Han (Aquaculture International, 2023)

A novel solar-activated chlorine dioxide process for atrazine degradation in drinking water - Han Chen; Tao Lin; Peifang Wang; Yuchen Wang; Wei Wei; Shuguang Zhu (Water Research, 2023)

Effect of non-simultaneous movement of adjacent twin-trapdoor on soil arching effect through discrete-element method simulation - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Han-Lin Wang; Fanyan Meng (Transportation Geotechnics, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Sulfonated polyhedral oligomeric silsesquioxane-cyclodextrin hybrid polymers for efficient removal of micropollutants from water - Hengye Li; Xingwei Han; Lin Zhang; Wenjie Yu; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

“Restorative-Repressive” perception on post-industrial parks based on artificial and natural scenarios: Difference and mediating effect - Fang Wei; Chuli Huang; Xuqing Cao; Shuhan Zhao; Tong Xia; Yijing Lin; Qisheng Han (Urban Forestry & Urban Greening, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Polycrystalline ZSM-5@Beta core–shell composites fabricated by a seed-directed approach: A catalyst to boosting light olefin production by ordered hierarchical cracking - Lei Han; Ruoyu Wang; Peng Wang; Yuchen Sha; Aiguo Zheng; Qiuqiao Jiang; Mudi Xin; Haitao Song; Wei Lin (Fuel, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Synthesis of porous dimethoxypillar[5]arene knitted β-cyclodextrin copolymers for efficient adsorption of organic micropollutants - Hengye Li; Xingwei Han; Wenjie Yu; Lin Zhang; Wenwen Bie; Meijie Wei; Zhongxia Wang; Fenying Kong; Wei Wang (Carbohydrate Polymers, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Protective Effect of Ergothioneine Against Stroke in Rodent Models - Wei-Yi Ong; Mei-Han Kao; Wai-Mui Cheung; Damien Meng-Kiat Leow; Irwin Kee-Mun Cheah; Teng-Nan Lin (NeuroMolecular Medicine, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Sialylation of cell surface glycoconjugates modulates cytosolic galectin-mediated responses upon organelle damage - I-Chun Weng; Hung-Lin Chen; Wei-Han Lin; Fu-Tong Liu (Glycoconjugate Journal, 2023)

Effects of dietary mannan oligosaccharides on growth, non-specific immunity, and intestinal health in juveniles of the Japanese sea cucumber (Apostichopus japonicus) - Xin Gao; Haojie Zhai; Libo Wei; Lidong Shi; Lin Yan; Zuxiang Peng; Wei Wang; Tongjun Ren; Yuzhe Han (Aquaculture International, 2023)

Substantial short- and long-term health effect due to PM2.5 and the constituents even under future emission reductions in China - Shengnan Xiang; Xiuwen Guo; Wenbin Kou; Xinran Zeng; Feifan Yan; Guangliang Liu; Yuanyuan Zhu; Yang Xie; Xiaopei Lin; Wei Han; Yang Gao (Science of The Total Environment, 2023)

Advances in the understanding of Blattodea evolution: Insights from phylotranscriptomics and spermathecae - Jin-lin Liu; Jia-wei Zhang; Wei Han; Yi-shu Wang; Shu-lin He; Zong-qing Wang (Molecular Phylogenetics and Evolution, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

The role of N6-methyladenosine modification in benzene-induced testicular damage and the protective effect of melatonin - Lin Han; Jingyu Wang; Lei Zhang; Jiaru Jing; Wei Zhang; Ziyan Liu; Ai Gao (Chemosphere, 2023)

Detection and quantification of Klebsiella pneumoniae in American bullfrog (Rana catesbeiana) by Taqman MGB probe real-time fluorescence quantitative PCR - Han Lin; Jingyang Sun; Jie Ma; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Removal of residual benzohydroxamic acid-lead complex from mineral processing wastewater by metal ion combined with gangue minerals - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Mengjie Tian; Chenyang Zhang; Ruohua Liu; Meirong Wu; Huanjun Bao; Wei Sun (Journal of Cleaner Production, 2023)

Fabrication of polyamide thin film nanocomposite membranes with enhanced desalination performance modified by silica nanoparticles formed in-situ polymerization of tetramethoxysilane - Yunbo Tong; Yulin Wei; Han Zhang; Lin Wang; Lingling Li; Fangkun Xiao; Congjie Gao; Guiru Zhu (Journal of Environmental Chemical Engineering, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Recoil suppression of deepwater drilling riser systems via static output feedback control with memory - Bao-Lin Zhang; Zhihui Cai; Wei Zhang; Feng-Bin Pang; Qing-Long Han; Xian-Ming Zhang (Ocean Engineering, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Genus unclassified_Muribaculaceae and microbiota-derived butyrate and indole-3-propionic acid are involved in benzene-induced hematopoietic injury in mice - Jingyu Wang; Lin Han; Ziyan Liu; Wei Zhang; Lei Zhang; Jiaru Jing; Ai Gao (Chemosphere, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Enrofloxacin exposure induces anxiety-like behavioral responses in zebrafish by affecting the microbiota-gut-brain axis - Dandan Tian; Wei Shi; Yihan Yu; Weishang Zhou; Yu Tang; Weixia Zhang; Lin Huang; Yu Han; Guangxu Liu (Science of The Total Environment, 2023)

Newly isolated halotolerant Aspergillus sp. showed high diesel degradation efficiency under high salinity environment aided with hematite - Sumbal Sajid; Víctor Resco de Dios; Obey Kudakwashe Zveushe; Farhan Nabi; Songrong Shen; Qianlin Kang; Lei Zhou; Lin Ma; Wei Zhang; Yulian Zhao; Ying Han; Faqin Dong (Journal of Hazardous Materials, 2023)

Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Li Wang; Chenyang Zhang; Ruohua Liu; Huanjun Bao; Meirong Wu; Gaogui Jing; Wei Sun (Journal of Cleaner Production, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Statistical optimization of hydrogen production from bio-methanol steam reforming over Ni-Cu/Al2O3 catalysts - Yi-Kai Chih; Wei-Hsin Chen; Siming You; Chun-Han Hsu; Hong-Ping Lin; Salman Raza Naqvi; Veeramuthu Ashokkumar (Fuel, 2023)

Identification of ISG15 in golden pompano, Trachinotus ovatus, and its role in virus and bacteria infections - Lin Huang; Yuan Cheng; Shuyu Han; Mingzhu Liu; Qing Yu; Hongling Wei; Jinzhao He; Pengfei Li (Fish & Shellfish Immunology, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Osteomodulin protects dental pulp stem cells from cisplatin-induced apoptosis in vitro - Ting Dong; Wen-zhen Lin; Xiao-han Zhu; Ke-yong Yuan; Li-li Hou; Zheng-wei Huang (Stem Cell Reviews and Reports, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

Longitudinal Abnormalities in Brain Structure in COVID-19 Patients - Xiaoxing Liu; Wei Yan; Tangsheng Lu; Ying Han; Lin Lu (Neuroscience Bulletin, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Unique Pharmacology, Brain Dysfunction, and Therapeutic Advancements for Fentanyl Misuse and Abuse - Ying Han; Lu Cao; Kai Yuan; Jie Shi; Wei Yan; Lin Lu (Neuroscience Bulletin, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Analysis of Influencing Factors of SST in Tropical West Indian Ocean Based on COBE Satellite Data - Chaoli Tang; Dewei Hao; Yuanyuan Wei; Fengmei Zhao; Han Lin; Xin Wu (Journal of Marine Science and Engineering, 2022)
The time-frequency domain analysis of the sea surface temperature (SST) in the tropical western Indian Ocean was conducted using wavelet analysis, cross wavelet transform (XWT), the Mann–Kendall (MK) test, and other methods based on COBE-SST data for the last 50 years (1974–2020). From the perspective of time-frequency combination, examining the data of precipitation, sea surface heat flux, total cloud cover, and long-wave radiation, helped contribute to exploring the periodic changes of SST. Moreover, the Western Hemisphere Warm Pool (WHWP) was selected to analyze the role of SST from 1974 to 2020. Present results have demonstrated that the SST in the western Indian Ocean was in a stage of rising, particularly in 1998. According to the fast Fourier transform of the filtered SST time series, the tropical western Indian Ocean SST has a short period of 3–6 years, a medium period of about 10 years, and a long period of 40 years. The SST in the tropical western Indian Ocean has a resonance period of 2–6 years with precipitation, a resonance period of 2–6 years with sea surface heat flux, a resonance period of 4–5 years with total cloud cover, and a resonance period of 2–5 years with long-wave radiation. Importantly, SST was negatively associated with precipitation, total cloud cover, and long-wave radiation, and positively for sea surface heat flux before 1997. Seasonal migration activities are significantly correlated with the WHWP and the tropical western Indian Ocean SST. The spatial lattice point correlation coefficient is generally from 0.6 to 0.9, and the inter-annual serial correlation value is more than 0.89. Furthermore, the two exist with a resonance period of 2–5 years.

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Optimizing the distribution and proportion of various active sites for better NH3-SCR property over Cu/SSZ-13 - Ziqian Liu; Han Jiang; Bin Guan; Yanfei Wei; Xingze Wu; He Lin; Zhen Huang (Environmental Science and Pollution Research, 2022)

Effects of Suspended Particles on Exopolysaccharide Secretion of Two Microalgae in Jinjiang Estuary (Fujian, China) - Jie Liu; Xiaoyu Han; Hui Xing; Yiting Nan; Jiahui Lin; Junming He; Sijia Chen; Yanfang Wei; Peiyong Guo (Journal of Marine Science and Engineering, 2022)
The effects of suspended particles (SP) of different concentrations and sizes on the secretion of exopolysaccharide (EPS) by Chlorella pyrenoidosa (C. pyrenoidosa) and Microcystis flos-aquae (M. flos-aquae) in Jinjiang Estuary, Fujian Province, China were studied in co-cultures of microalgae and SP. The results show that the SP concentration has an “inhibit–promote–inhibit” effect on the secretion of EPS by C. pyrenoidosa, whereby there is an optimal concentration of SP corresponding to the largest amount of EPS secreted by C. pyrenoidosa. Low concentrations had no significant effect on the secretion of EPS from M. flos-aquae (p > 0.05), whereas higher concentrations had an inhibitory effect. The C. pyrenoidosa EPS content was found to be significantly decreased in response to SP of small particle sizes (0–75 and 75–120 μm) and significantly increased for SP of large particle sizes (120–150 and 150–500 μm). Small particle sizes (0–75 and 75–120 μm) were found to be beneficial to the secretion of EPS from M. flos-aquae, and the promotion of EPS secretion gradually decreased with the increase in SP particle size. However, when the particle size was too large (120–150 and 150–500 μm), SP had no significant effect on EPS secretion. This study is helpful for understanding the microalgae EPS secretion response to SP and provides a scientific basis for studying the mechanism of EPS secretion by algae and the effect of SP on eutrophication of the estuary.

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Mild encephalitis/encephalopathy with a reversible splenial lesion associated with respiratory syncytial virus infection in infants - Xue-Lin Li; Jinming Han; Zhong-Rui Yan; Bing-Wei Zhang; Hai-Yang Wang (Journal of NeuroVirology, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Analysis of slug interference tests conducted in an artificial fracture - Yunfeng Dai; Yanrong Zhao; Jin Lin; Jiangbo Han; Xiaomin Sun; Wei Li; Jiufu Liu (Hydrogeology Journal, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Photosensitive hydrogels: from structure, mechanisms, design to bioapplications - Wenhui Ji; Qiong Wu; Xisi Han; Wei Zhang; Wei Wei; Liang Chen; Lin Li; Wei Huang (Science China Life Sciences, 2020)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Microbiome technology empowers the development of traditional Chinese medicine - Hongtao Liu; Junping Zheng; Hsin-Chih Lai; Baifei Hu; Lin Zhu; Elaine Lai-Han Leung; Hong Wei (Science China Life Sciences, 2020)

Complete genome sequence of a novel recombinant avian leukosis virus isolated from a three-yellow chicken - Tao Sun; Ximei Wang; Wei Han; Xiaoling Ma; Weili Yin; Baohai Fang; Xiao Lin; Yang Li (Archives of Virology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

On the Sensitivity of Typhoon Wave Simulations to Tidal Elevation and Current - Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
The sensitivity of storm wave simulations to storm tides and tidal currents was investigated using a high-resolution, unstructured-grid, coupled circulation-wave model (Semi-implicit Cross-scale Hydroscience Integrated System Model Wind Wave Model version III (SCHISM-WWM-III)) driven by two typhoon events (Typhoons Soudelor and Megi) impacting the northeastern coast of Taiwan. Hourly wind fields were acquired from a fifth-generation global atmospheric reanalysis (ERA5) and were used as meteorological conditions for the circulation-wave model after direct modification (MERA5). The large typhoon-induced waves derived from SCHISM-WWM-III were significantly improved with the MERA5 winds, and the peak wave height was increased by 1.0–2.0 m. A series of numerical experiments were conducted with SCHISM-WWM-II and MERA5 to explore the responses of typhoon wave simulations to tidal elevation and current. The results demonstrate that the simulated significant wave height, mean wave period and wave direction for a wave buoy in the outer region of the typhoon are more sensitive to the tidal current but less sensitive to the tidal elevation than those for a wave buoy moored in the inner region of the typhoon. This study suggests that the inclusion of the tidal current and elevation could be more important for typhoon wave modeling in sea areas with larger tidal ranges and higher tidal currents. Additionally, the suitable modification of the typhoon winds from a global atmospheric reanalysis is necessary for the accurate simulation of storm waves over the entire region of a typhoon.

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Anomalous distribution of distinctive water masses over the Carlsberg Ridge in May 2012 - Hailun He; Yuan Wang; Xiqiu Han; Yanzhou Wei; Pengfei Lin; Zhongyan Qiu; Yejian Wang (Ocean Science, 2020)
In May 2012, we conducted a hydrographic survey over the Carlsberg Ridge in the northwest Indian Ocean. In this paper, we use these station data, in combination with some free-floating Argo profiles, to obtain the sectional temperature and salinity fields, and subsequently, the hydrographic characteristics are comprehensively analyzed. Through the basic T–S diagram, three salty water masses, Arabian Sea High-Salinity Water, Persian Gulf Water, and Red Sea Water, are identified. The sectional data show a clear ventilation structure associated with Arabian Sea High-Salinity Water. The 35.8 psu salty water sinks at 6.9∘ N and extends southward to 4.4∘ N at depths around the thermocline, where the thermocline depth is in the range of 100 to 150 m. This salty thermocline extends much further south than climatology indicates. Furthermore, the temperature and salinity data are used to compute the absolute geostrophic current over the specific section, and the results show mesoscale eddy vertical structure different from some widely used oceanic reanalysis data. We also find a west-propagating planetary wave at 6∘ N, and the related features are described in terms of phase speed and horizontal and vertical structures.

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Baicalein attenuates caspase-independent cells death via inhibiting PARP-1 activation and AIF nuclear translocation in cerebral ischemia/reperfusion rats - Wei-Han Li; Ying-Lin Yang; Xiao Cheng; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Apoptosis, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Dynamic Alterations of Brain Injury, Functional Recovery, and Metabolites Profile after Cerebral Ischemia/Reperfusion in Rats Contributes to Potential Biomarkers - Xiao Cheng; Ying-Lin Yang; Wei-Han Li; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Journal of Molecular Neuroscience, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Association between tooth loss and gray matter volume in cognitive impairment - Chia-Shu Lin; Hsiao-Han Lin; Shin-Woei Fann; Wei-Ju Lee; Ming-Lun Hsu; Shuu-Jiun Wang; Jong-Ling Fuh (Brain Imaging and Behavior, 2020)

Numerical Simulation of Large Wave Heights from Super Typhoon Nepartak (2016) in the Eastern Waters of Taiwan - Shih-Chun Hsiao; Hongey Chen; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Wen-Dar Guo; Yung-Ming Chen; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
Super Typhoon Nepartak (2016) was used for this case study because it is the most intense typhoon that made landfall in Taiwan in the past decade. Winds extracted from the Climate Forecast System version 2 (CFSV2) and ERA5 datasets and merged with a parametric typhoon model using two hybrid techniques served as the meteorological conditions for driving a coupled wave-circulation model. The computed significant wave heights were compared with the observations recorded at three wave buoys in the eastern waters of Taiwan. Model performance in terms of significant wave height was also investigated by employing the CFSV2 winds under varying spatial and temporal resolutions. The results of the numerical experiments reveal that the simulated storm wave heights tended to decrease significantly due to the lower spatial resolution of the hourly winds from the CFSV2 dataset; however, the variations in the storm wave height simulations were less sensitive to the temporal resolution of the wind field. Introducing the combination of the CFSV2 and the parametric typhoon winds greatly improved the storm wave simulations, and similar phenomena can be found in the exploitation of the ERA5 dataset blended into the parametric wind field. The overall performance of the hybrid winds derived from ERA5 was better than that from the CFSV2, especially in the outer region of Super Typhoon Nepartak (2016).

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Alterations of Copper and Zinc Homeostasis in Acute Appendicitis and the Clinical Significance - Wenhao Lin; Wei Han; Ke Wen; Sunhua Huang; Yao Tang; Zhexuan Lin; Ming Han (Biological Trace Element Research, 2019)

Netrin-1 promotes the collective cell migration of liver cancer cells in a 3D cell culture model - Ping Han; Jingmei Liu; Yu Lei; Zhuoying Lin; Dean Tian; Wei Yan (Journal of Physiology and Biochemistry, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Cloning and overexpression of the ascorbate peroxidase gene from the yam (Dioscorea alata) enhances chilling and flood tolerance in transgenic Arabidopsis - Zhihua Chen; Hsueh-Han Lu; Shumei Hua; Kuan-Hung Lin; Ningdan Chen; Yangwen Zhang; Ziyi You; Yun-Wei Kuo; Shi-Peng Chen (Journal of Plant Research, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Different removal efficiency of disinfection-byproduct precursors between dichloroacetonitrile (DCAN) and dichloroacetamide (DCAcAm) by up-flow biological activated carbon (UBAC) process - Han Chen; Tao Lin; Wei Chen; Hang Xu; Hui Tao (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Natural CAC chemopreventive agents from Ilex rotunda Thunb. - Yueqing Han; Lin Zhang; Wei Li; Xinran Liu; Jiao Xiao; Gang Chen; Ning Li (Journal of Natural Medicines, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Paleogeomorphology restoration and the controlling effects of paleogeomorphology on karst reservoirs: a case study of an ordovician-aged section in Tahe oilfield, Tarim Basin, China - Changcheng Han; Chengyan Lin; Ting Wei; Chunmei Dong; Lihua Ren; Xianguo Zhang; Li Dong; Xu Zhao (Carbonates and Evaporites, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Association between prenatal nickel exposure and preterm low birth weight: possible effect of selenium - Xiaojie Sun; Yangqian Jiang; Wei Xia; Shuna Jin; Wenyu Liu; Xin Lin; Hongxiu Liu; Xiaomei Chen; Yang Peng; Han Li; Bin Lu; Shunqing Xu; et al. (Environmental Science and Pollution Research, 2018)

Tacrine(10)-hupyridone, a dual-binding acetylcholinesterase inhibitor, potently attenuates scopolamine-induced impairments of cognition in mice - Huixin Chen; Siying Xiang; Ling Huang; Jiajia Lin; Shengquan Hu; Shing-Hung Mak; Chuang Wang; Qinwen Wang; Wei Cui; Yifan Han (Metabolic Brain Disease, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Characterization of the complete chloroplast genome sequence of Lysionotus pauciflorus (Gesneriaceae) - Ting Ren; Wei Zheng; Kai Han; Shuyun Zeng; Jianhua Zhao; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Wind and salt spray alter tree shape and dry mass density in Casuarina equisetifolia L. - Yongming Lin; Jian Li; Jonathan D. Bakker; Han Lin; Can Chen; Wei Hong; Loretta Fisher; Chengzhen Wu; Tao Hong; Haojun Deng; Guangshuai Zhang; Kun Du (Trees, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

BM-MSCs and Bio-Oss complexes enhanced new bone formation during maxillary sinus floor augmentation by promoting differentiation of BM-MSCs - Qian Zhou; Bo-Han Yu; Wei-Cai Liu; Zuo-Lin Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

Controversial opinion: evaluation of EGR1 and LAMA2 loci for high myopia in Chinese populations - Fang-yu Lin; Zhu Huang; Ning Lu; Wei Chen; Hui Fang; Wei Han (Journal of Zhejiang University-SCIENCE B, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Blockade of the Activation of T Cells Around β-Cell by the Targeted CTLA-4 Ig at the Surface of β-Cell - Wei Qu; Lin Li; Chendong Han; Meihua Li; Jing Wang; Chaohui Yin; Jing Zhang; Zhaoshun Jiang (Cell Biochemistry and Biophysics, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Halorussus ruber sp. nov., isolated from an inland salt lake of China - Wei-Dong Xu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Kun Yang (Archives of Microbiology, 2015)

A novel silent deletion, an insertion mutation and a nonsense mutation in the TCOF1 gene found in two Chinese cases of Treacher Collins syndrome - Yan Wang; Xiao-Juan Yin; Tao Han; Wei Peng; Hong-Lin Wu; Xin Liu; Zhi-Chun Feng (Molecular Genetics and Genomics, 2014)

Indoor/outdoor pollution level and personal inhalation exposure of polycyclic aromatic hydrocarbons through biomass fuelled cooking - Guofeng Shen; Yanyan Zhang; Siye Wei; Yuanchen Chen; Chunli Yang; Pengchuan Lin; Han Xie; Miao Xue; Xilong Wang; Shu Tao (Air Quality, Atmosphere & Health, 2014)

Description of Algoriphagus taiwanensis sp. nov., a xylanolytic bacterium isolated from surface seawater, and emended descriptions of Algoriphagus mannitolivorans, Algoriphagus olei, Algoriphagus aquatilis and Algoriphagus ratkowskyi - Mariyam Shahina; Asif Hameed; Shih-Yao Lin; Wei-An Lai; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

FP-receptor gene silencing ameliorates myocardial fibrosis and protects from diabetic cardiomyopathy - Wen-yuan Ding; Lin Liu; Zhi-hao Wang; Meng-xiong Tang; Yun Ti; Lu Han; Lei Zhang; Yun Zhang; Ming Zhong; Wei Zhang (Journal of Molecular Medicine, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Purification and characterization of a laccase from Coprinopsis cinerea in Pichia pastoris - Bo Wang; Lijuan Wang; Yaqiu Lin; Qing Han; Jing Han; Jianjie Gao; Yongsheng Tian; Wei Zhao; Rihe Peng; Quanhong Yao (World Journal of Microbiology and Biotechnology, 2014)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Predation pressure induced by seasonal fishing moratorium changes the dynamics of subtropical Cladocera populations - Qiuqi Lin; Pingping Zhao; Qiuting Wu; Zhihong Wei; Huiming Li; Bo-Ping Han (Hydrobiologia, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Comparing removal of trace organic compounds and assimilable organic carbon (AOC) at advanced and traditional water treatment plants - Jie-Chung Lou; Chung-Yi Lin; Jia-Yun Han; Wei-Biu Tseng; Kai-Lin Hsu; Ting-Wei Chang (Environmental Monitoring and Assessment, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Dexamethasone attenuates development of monocrotaline-induced pulmonary arterial hypertension - Wei Wang; Yu-lin Wang; Xiao-ying Chen; Yu-tang Li; Wei Hao; You-peng Jin; Bo Han (Molecular Biology Reports, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Isolation and characterization of a new bacteriophage MMP17 from Meiothermus - Lianbing Lin; Jian Han; Xiuling Ji; Wei Hong; Li Huang; Yunlin Wei (Extremophiles, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Efficient shoot regeneration andAgrobacterium-mediated transformation ofBrassica juncea - Zhang Yuxiu; Xu Jin; Han Lu; Wei Wei; Guan Ziqiu; Cong Lin; Chai Tuanyao (Plant Molecular Biology Reporter, 2006)

Effects of Growth Regulators on Direct Flowering of Isolated Ginseng Buds in vitro - Choun-Sea Lin; Chang-Tsern Chen; Han-Wen Hsiao; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Antimicrobial screening and active compound isolation from marine bacterium NJ6-3-1 associated with the sponge Hymeniacidon perleve - Li Zheng; Haimin Chen; Xiaotian Han; Wei Lin; Xiaojun Yan (World Journal of Microbiology and Biotechnology, 2005)

Development of Linum flavum hairy root cultures for production of coniferin - Han-wei Lin; Kian H. Kwok; Pauline M. Doran (Biotechnology Letters, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)